Successful Treatment of Scrub Typhus-Associated Hemophagocytic Lymphohistiocytosis With Chloramphenicol: Report of 3 Pediatric Cases and Literature Review. Issue 8 (February 2016) - Zhou, Yong-Hai; Xia, Fang-Qing; Van Poucke, Sven; Zheng, Ming-Hua
Abstract : Abstract: Scrub typhus is caused by Orientia tsutsugamushi . Any delay in diagnosis can result in delayed treatment and severe complications, including secondary hemophagocytic lymphohistiocytosis, which is rare but potentially fatal. In this paper, the authors present 3 cases of secondary hemophagocytic lymphohistiocytosis associated with scrub typhus, successfully treated with chloramphenicol without additional antineoplastic therapy. All patients cured and achieved complete resolution. This report highlights the effectiveness of chloramphenicol without the need for chemotherapy in the treatment of scrub typhus-associated hemophagocytic lymphohistiocytosis in a pediatric population under the age of 8 years.